Analysis of confidentiality algorithms in different mobile generations - Jassim, Khalid Fadhil; Alshaikhli, Imad Fakhri Taha (2017)
In past years, a variety of Mobile technology generations have been adopted in mobile communication systems. Various sensitive information (e.g. emails, bank transactions, voice calls, ... ) was exchanged via the mobile systems. The protection of information confidentiality became a serious problem for the customers of these systems. Security solutions such as confidentiality cipher algorithms proposed to protect the transmissions in different mobile generations. The proposed cipher algorithms like A5/1 cipher, SNOW 3G cipher, ZUC cipher, and AES cipher were designed for securing mobile systems. This paper provides analysis study of operations and specifications for these cipher algorithms, and investigating the cryptanalysis methods which can be employed to attack these cipher algorithms